Extra-tidal structures around the Gaia Sausage candidate globular cluster NGC 6779 (M56) - Piatti, Andres Eduardo (2019)
We present results on the stellar density radial profile of the outer regions of NGC6779, a Milky Way globular cluster recently proposed as a candidate member of the Gaia Sausage structure, a merger remnant of a massive dwarf galaxy with the Milky Way.Taking advantage of the Pan-STARRS PS1 public astrometric and photometric catalogue,we built the radial profile for the outermost cluster regions using horizontal branch and main sequence stars, separately,  in order to probe for different profile trends because of difference stellar masses. Owing to its relatively close location to the Galactic plane, we have carefully treatedthe chosen colour-magnitude regions properly correcting them by the amount ofinterstellar extinction measured along the line-of-side of each star, as well as cleaned themfrom the variable field star contamination observed across the cluster field.  In the region spanning from the tidal to the Jacobi radii the resulting radial profiles show a diffuseextended halo, with an average power law slope of -1. While analysingthe relationships between the Galactocentric distance, the half-mass density, the half-lightradius, the slope of the radial profile of the outermost regions, the internal dynamical evolutionarystage, among others, we found that NGC6779 shows structural properties similar to those of the remaining  Gaia  Sausage candidate globular clusters, namely, they are massive clusters  (>10^5Mo) in a moderately early dynamical evolutionary stage, with  observed extra-tidal structures.